Paternally‐biased gene expression follows kin‐selected predictions in female honey bee embryos. Issue 8 (24th April 2020) - Smith, Nicholas M. A.; Yagound, Boris; Remnant, Emily J.; Foster, Charles S. P.; Buchmann, Gabriele; Allsopp, Michael H.; Kent, Clement F.; Zayed, Amro; Rose, Stephen A.; Lo, Kitty; Ashe, Alyson; Harpur, Brock A.; et al.
Abstract: The Kinship Theory of Genomic Imprinting (KTGI) posits that, in species where females mate with multiple males, there is selection for a male to enhance the reproductive success of his offspring at the expense of other males and his mating partner. Reciprocal crosses between honey bee subspecies show parent‐of‐origin effects for reproductive traits, suggesting that males modify the expression of genes related to female function in their female offspring. This effect is likely to be greater in the Cape honey bee ( Apis mellifera capensis ), because a male's daughters have the unique ability to produce female offspring that can develop into reproductive workers or the next queen without mating. We generated reciprocal crosses between Capensis and another subspecies and used RNA‐seq to identify transcripts that are over‐ or underexpressed in the embryos, depending on the parental origin of the gene. As predicted, 21 genes showed expression bias towards the Capensis father's allele in colonies with a Capensis father, with no such bias in the reciprocal cross. A further six genes showed a consistent bias towards expression of the father's allele across all eight colonies examined, regardless of the direction of the cross. Consistent with predictions of the KTGI, six of the 21 genes are associated with female reproduction. No gene consistently showed overexpression of the maternal allele.